GAMBARAN MANUSKRIP AL-QUR’AN HJ. RIPPUN DI DESA PAMBUSUANG KABUPATEN POLEWALI MANDAR: (Studi Kodikologi dan Filologi) - IIN SRIWATI; Harlisa; Syarif (EL-ADABI : Jurnal Studi Islam, 2023)
The qualitative method is the method used in this study and is based on the result of direct observation and interviews. The main speakers are Syarkawi and Sya'rawi who are the next manuscript holder (son of Hj. Mul Azam). This research is also based on scientific research books and journals. Codcological and Philology studies are the approach used in this study. The physical condition of the manuscript is still fairly good. This study also revealed the aspects of Qira'at which was found that this manuscript uses Qira'at Imam 'Ashim and Ibn Kathir. The aspect of RASM's writing, it was found that Hj. Rippun's manuscript in Pambusuang followed the rules of Utsmani rasm writing compiled by Imam as-Suyuthi in the book of Al-Itqan Fi Ulum Al- Qur'an. Regarding the results of this manuscript study was taken from the history that was told directly from the descendants of the author so that this manuscript had no concrete evidence of the truth.. Looking at the other side, in this manuscript there are various illuminations, waqaf signs, juz and other symbols and regarding separators between verses no verse number is found so that it makes it a little difficult to determine the verse.